Catastrophic health expenditure and its associated factors among adult cancer patients in hospital Universiti Sains Malaysia - Zaman, Muhammad Abdul Hafiz Kamarul (2024)
Introduction:ِ Highِ out-of-pocketِ (OOP)ِ healthِ expendituresِ dueِ toِ costlyِ treatmentsِ andِ prolongedِ care,ِ posesِ aِ substantialِ riskِ ofِ catastrophicِ healthِ expenditureِ (CHE)ِ forِ households.ِ Catastrophicِ healthِ expenditureِ amongِ householdsِ affectedِ byِ cancerِ canِ beِ devastatingِ forِ familiesِ alreadyِ facingِ theِ emotionalِ andِ psychologicalِ challengesِ ofِ cancerِ diagnosisِ andِ treatment. Objective: Theِ purposeِ ofِ thisِ studyِ wasِ toِ determineِ theِ proportionِ ofِ CHEِ andِ itsِ associatedِ factorsِ amongِ adultِ cancerِ patientsِ atِ Hospitalِ Universitِi Sainsِ Malaysia. Methodology:ِ Aِ cross-sectionalِ studyِ wasِ conductedِ withِ 209ِ adultِ cancerِ patientsِ atِ Hospitalِ Universitِi Sainsِ Malaysiaِ fromِ Decemberِ 2023ِ toِ Aprilِ 2024.ِ Participantsِ wereِ selectedِ usingِ systematicِ randomِ samplingِ andِ dataِ wereِ collectedِ throughِ guidedِ face-to- faceِ interviews.ِ Theِ proformaِ usedِ includedِ sectionsِ onِ sociodemographicِ details,ِ diseaseِ information,ِ householdِ details,ِ andِ expenditureِ andِ income.ِ Theِ primaryِ outcomeِ wasِ theِ proportionِ ofِ patientsِ experiencingِ CHE,ِ definedِ asِ out-of-pocketِ (OOP)ِ healthِ expensesِ exceedingِ 10%ِ ofِ householdِ income.ِ Multipleِ logisticِ regressionِ analysisِ wasِ employedِ toِ identifyِ factorsِ associatedِ withِ CHE. Results:ِ Theِ studyِ revealedِ thatِ 15.3%ِ ofِ theِ participantsِ experiencedِ CHE.ِ Significantِ factorsِ associatedِ withِ CHEِ includedِ ethnicity,ِ educationِ level,ِ GLِ status,ِ andِ theِ employmentِ statusِ ofِ theِ householdِ head.ِ Non-Malayِ patientsِ hadِ 6.63ِ timesِ theِ oddsِ ofِ experiencingِ CHEِ comparedِ toِ Malayِ patientsِ (p-value=0.013,ِ 95%ِ CI:ِ 1.49,29.57).ِ Patientsِ withِ primaryِ schoolِ educationِ orِ belowِ hadِ 9.56ِ timesِ theِ oddsِ ofِ experiencingِ CHEِ comparedِ toِ thoseِ withِ tertiaryِ educationِ (p-value=0.005,ِ 95%ِ CI:ِ 2.01,45.57).ِ Patientsِ withoutِ GLِ wereِ 4.81ِ timesِ moreِ likelyِ toِ experienceِ CHEِ thanِ thoseِ withِ GLِ (p- value=0.008,ِ 95%ِ CI:ِ 1.51,15.34).ِ Householdsِ whereِ theِ headِ wasِ unemployedِ hadِ 6.55ِ timesِ theِ oddsِ ofِ experiencingِ CHEِ comparedِ toِ thoseِ withِ employedِ headsِ (p- value=0.014,ِ 95%ِ CI:ِ 1.46,29.35). Conclusion:ِ Theِ studyِ highlightsِ significantِ sociodemographicِ andِ householdِ factorsِ contributingِ toِ CHEِ amongِ adultِ cancerِ patientsِ inِ Hospitalِ Universitِi Sainsِ Malaysia.ِ Theseِ findingsِ emphasizeِ theِ needِ forِ targetedِ interventionsِ toِ mitigateِ financialِ burdensِ onِ cancerِ patients,ِ particularlyِ focusingِ onِ education,ِ employment,ِ andِ financialِ supportِ mechanisms.